Pengukuran Dampak Nilai Tukar Terhadap Produksi dan Pendapatan Petani Padi - Budiman Hutabarat (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1996)
Agricultural parity price can be used as proxy for real farm income which in turn incites farmers' interest to produce. The paper intends to estimate the magnitude of parity price impact on farmer's production and net income. It is based on research undertaken through survey method by interviewing many farmers in rice production centers of North Sumatera, Central Java, and Nusa Tenggara Timur. The total number of samples was 316 people. The survey was conducted in July-August 1994 and October - November 1994. The paper concludes that agricultural parity price has positive impact on production of rice with the magnitude ranging from 0.07 to 0.56. Similar conclusion applies to net farmer income with the magnitude ranging from 0.14 to 1.45. Thus, if farmers enthusiasm needs to be generated to product rice, agricultural parity price will be an effective mean. The agricultural parity price should not only consider the prices of production input but also those of other consumption commodities.